Perioperatif Operasi pada Fetus - Yusuf Raksawardana; Djayanti Sari; Pinter Hartono (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Anesthetic risk is inversely proportional to age, with neonates having a higher risk of mortality and morbidity compared to adults. Understanding these differences is essential for appropriate perioperative evaluation, preparation, planning, and anesthetic management in neonatal and fetal surgery. Advances in prenatal diagnostic techniques have improved the accuracy of fetal anomaly detection, enabling timely surgical intervention when indicated. Fetal surgery includes minimally invasive procedures, open fetal surgery, and ex utero intrapartum treatment (EXIT) procedures. Surgical intervention is considered when congenital abnormalities threaten fetal survival or lead to severe postnatal morbidity.